2005
DOI: 10.1007/s11211-005-3393-3
|View full text |Cite
|
Sign up to set email alerts
|

Justice in Health Care Decision-Making: Patients’ Appraisals of Health Care Providers and Health Plan Representatives

Abstract: This study describes the development of two versions of a Health Care Justice Inventory (HCJI). One version focuses on patients' interactions with their providers (HCJI-P) and the other focuses on patients' interactions with the representatives of their health plans (HCJI-HP). Each version of the HCJI assesses patients' appraisals of their interactions (with either their Provider or representatives of their Health Plan) along three common dimensions of procedural justice: Trust, Impartiality, and Participation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 28 publications
(54 reference statements)
0
26
0
Order By: Relevance
“…Similar knowledge gaps concern the required procedures and the rights of individuals subject to a hold. Available research suggests that if individuals believe they have been treated fairly and given a voice, their satisfaction and willingness to adhere to treatment may be enhanced (17)(18)(19), but the comparative effect on public safety is largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Similar knowledge gaps concern the required procedures and the rights of individuals subject to a hold. Available research suggests that if individuals believe they have been treated fairly and given a voice, their satisfaction and willingness to adhere to treatment may be enhanced (17)(18)(19), but the comparative effect on public safety is largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…This paper seeks to compare Medicaid patients' evaluations of their inpatient acute care with the evaluations of private-pay patients. Only one other study has used patients' appraisals to evaluate social justice in healthcare: Fondacaro et al (2005) employed similar core constructs and items as in our instrument (e.g., involvement in decision making, behaviors of nurses and doctors). Their ''Health Care Justice Inventory'' focused on three common dimensions of procedural justice: trust, impartiality, and participation.…”
Section: Their Care Experiencementioning
confidence: 99%
“…[52] According to Fondacaro et al, "one of the most intriguing findings in the social justice literature is that people seem to care as much or more about how they are treated in the course of decision making (procedural justice) as they do about the decision outcome (distributive justice)." [53] Therefore, for government policy makers who are faced with decisions about whether to reimburse drugs within the confines of limited resources a goal should be fairness. Furthermore, a study conducted by Murphy-Berman et al, found that individuals who felt that they were treated fairly, with regards to treatment decisions, had decreased levels of anger, and increased levels of pride.…”
Section: Negotiating Between the Tensionsmentioning
confidence: 99%
“…It is thought that trust and satisfaction in health plans "can help providers who must increasingly make treatment decisions in the context of limited resources." [53] A legitimate and fair process is characterized by inclusiveness, transparency, and responsiveness. A fair process would include stakeholders in the deliberative process i.e., patients, public, and industry [51].…”
Section: Negotiating Between the Tensionsmentioning
confidence: 99%